Analisis Pemikiran Paul F. Knitter Untuk Mengatasi Masalah Kemiskinan Di Toraja - Ra'ba Bara' Tiku, Seruni (Indonesian Journal of Religious, 2023)
The Torajan community faces complex challenges related to poverty, despite having strong cultural traditions and social solidarity. Factors such as limited infrastructure, high customary costs, and economic inequality exacerbate the socio-economic conditions in the region. This study seeks to analyze Paul Knitter’s thoughts, particularly the soteriocentric correlational dialogue approach, as a response to these poverty challenges. By employing a literature review method specifically textual and critical analyses of Knitter’s works this study examines key texts, such as One Earth Many Religions, along with statistical reports and literature on Torajan local traditions. The findings indicate that Knitter's approach is highly relevant in the context of Toraja. The religious diversity in the region can serve as a foundation for collaboration to address poverty through soteriocentric correlational dialogue, where dialogue is implemented through tangible actions focused on societal welfare and justice. This study aims to make a significant contribution to the development of interfaith dialogue and evaluate the relevance of Paul F. Knitter’s ideas in addressing the poverty challenges faced by the Torajan community.   Masyarakat Toraja menghadapi tantangan kemiskinan yang kompleks, meskipun memiliki tradisi budaya dan solidaritas sosial yang kuat. Faktor-faktor seperti keterbatasan infrastruktur, biaya adat yang tinggi, dan ketimpangan ekonomi memperparah kondisi kemiskinan di wilayah tersebut. Penelitian ini menganalisis pemikiran Paul Knitter, khususnya pendekatan dialog korelasional yang soteriosentris untuk merespons tantangan kemiskinan tersebut. Dengan menggunakan metode studi literatur yaitu analisis teks dan analisis kritis terhadap pemikiran Paul F. Knitter, penelitian ini mengkaji karya-karya utama Knitter, seperti Satu Bumi Banyak Agama, serta laporan statistik dan literatur tentang tradisi lokal Toraja. Hasil penelitian menunjukkan bahwa pendekatan Knitter sangat relevan dalam konteks Toraja. Keberagaman agama di Toraja dapat menjadi sarana kerjasama untuk mengatasi masalah kemiskinan dengan menggunakan pendekatan dialog korelasional yang soteriosenttris di mana dialog dilakukan dengan hasil kerja nyata dengan fokus kepada kesejahteraan dan keadilan dalam masyarakat. Penelitian ini bertujuan untuk memberikan kontribusi dalam pengembangan dialog antaragama serta mengevaluasi relevansi pemikiran Paul F. Knitter dalam mengatasi kemiskinan di Toraja.